具有手脚融合功能的步行机器人的手部结构设计 - 潘春梅; 王良文; 李爱敏; 穆小奇; 李群涛; 苏伟伟 (Jixie chuandong)
Based on the introduces of the overall structure for walking robot with integrated functions of hands and feet,the overall design proposal of robot hand is described.The basic design requirements of the hand are explained.The selection of the drive mode and transmission device,the calculat ion of the driving torque and the power for the hand,and the design process of the hand structure are described in detail.